2019
DOI: 10.1111/aor.13480
|View full text |Cite
|
Sign up to set email alerts
|

High‐permeability alternatives to current dialyzers performing both high‐flux hemodialysis and postdilution online hemodiafiltration

Abstract: Most high-flux dialyzers can be used in both hemodialysis (HD) and online hemodiafiltration (OL-HDF). However, some of these dialyzers have higher permeability and should not be prescribed for OL-HDF to avoid high albumin losses. The aim of this study was to compare the safety and efficacy of a currently used dialyzer in HD and OL-HDF with those of several other high permeability dialyzers which should only be used in HD. A prospective, single-center study was carried out in 21 patients. Each patient underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 29 publications
9
40
0
2
Order By: Relevance
“…Kirsch et al 7 Garcia-Prieto et al 8 Maduell et al 9 The present study (Table 5). These studies were performed for quite short-term treatment; therefore, the real effectiveness of MCO-HD in removals of middle-molecule uremic toxins is still not firmly established.…”
Section: Studiessupporting
confidence: 50%
See 1 more Smart Citation
“…Kirsch et al 7 Garcia-Prieto et al 8 Maduell et al 9 The present study (Table 5). These studies were performed for quite short-term treatment; therefore, the real effectiveness of MCO-HD in removals of middle-molecule uremic toxins is still not firmly established.…”
Section: Studiessupporting
confidence: 50%
“…With limitations of high-volume postdilution ol-HDF, HD with the new type of dialyzer, which has larger pore size than standard high-flux dialyzer, might provide better removal of protein-bound and middle-molecule uremic toxins. [7][8][9] Medium cut-off (MCO) from Europe and super high-flux (SHF) such as PES 17D alpha (PES) from Japan are two new large pore size dialyzers. Very few studies regarding MCO-HD were performed as a shortterm study and did not examine the effectiveness in removals of protein-bound uremic toxins.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, they can be explained by the dialyzer used in the comparison with the HDF technique, as Kirsch et al 3 and Garcia-Prieto et al 4 used a Helixone membrane while Reque et al 13 and Belmouaz et al 14 used polyamide membranes. Maduell et al 5,15 showed small differences in removal performance when comparing eight different high-flux dialyzers in post-HDF. On the other hand, the way in which HDF is carried out is extremely important because parameters such as Qb, replacement volume, convective volume, Q uf , or FF can potentially influence the removal capacity of the technique.…”
Section: T a B L E 3 (Continued)mentioning
confidence: 99%
“…Belmouaz et al 14 obtained similar results. However, Garcia-Prieto et al 4 and Maduell et al 5,[15][16] reported that β 2 -microglobulin, myoglobin, α 1 -microglobulin, prolactin, and free immunoglobulin light chain reduction ratios were higher with HDF.…”
Section: Introductionmentioning
confidence: 98%
“…Francisco Maduell et al of the Hospital Clínic Barcelona, Barcelona, Spain compared the safety and efficacy of a currently used dialyzer in hemodialysis (HD) and online hemodiafiltration (OL‐HDF) with those of several other high permeability dialyzers which should only be used in HD. A prospective, single‐center study was carried out in 21 patients.…”
Section: Renal Support and Dialysismentioning
confidence: 99%